Pengaruh Pemberian Onde-Onde Ubi Ungu Isi Hati Ayam dengan Penambahan Tepung Kacang Hijau pada Siswi Anemia SMAN 1 Liwa, Lampung Barat 2025 - Ryan Agusta; Afriyana Siregar; Sartono; Eliza (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Anemia is a pressing health problem worldwide, especially in developing countries like Indonesia. This condition occurs when the hemoglobin (Hb) level in the blood is below normal, disrupting the oxygen transport process to body tissues. The aim was to determine the effect of giving purple sweet potato onde-onde on increasing hemoglobin in students of SMA 1 Liwa, West Lampung 2025 who suffer from anemia. This study used a quasi-experimental design with a pretest-posttest control group design. The subjects were 60 female adolescents suffering from anemia at SMA 1 Liwa, West Lampung 2025 who were divided into treatment and comparison groups. The treatment group was given purple sweet potato onde-onde twice a day, each time giving 60 grams for 10 consecutive days. The data collected included hemoglobin levels, macronutrient intake, and iron, and were analyzed using appropriate statistical tests. Results The average hemoglobin level before treatment was 10.85 g/dl and after treatment was 11.94 g/dl with an average decrease of 1.090 g/dl. The results of the paired t-test showed a p-value of 0.001 (<0.05) which indicates that there is an effect of giving purple sweet potato onde-onde filled with chicken liver with the addition of green bean flour on increasing hemoglobin levels in students of SMA 1 Liwa, West Lampung 2025 who suffer from anemia. There is an effect of giving purple sweet potato onde-onde on increasing hemoglobin in students of SMA 1 Liwa, West Lampung 2025 who suffer from anemia.